Disease patterns in late-onset ulcerative colitis: Results from the IG-IBD "AGED study". Issue 1 (January 2017) - Fries, Walter; Viola, Anna; Manetti, Natalia; Frankovic, Iris; Pugliese, Daniela; Monterubbianesi, Rita; Scalisi, Giuseppe; Aratari, Annalisa; Cantoro, Laura; Cappello, Maria; Samperi, Leonardo; Saibeni, Simone; et al.
Abstract: Background: Late-onset UC represents an important issue for the near future, but its outcomes and relative therapeutic strategies are yet poorly studied. Aim: To better define the natural history of late-onset ulcerative colitis. Methods: In a multicenter retrospective study, we investigated the disease presentation and course in the first 3 years in 1091 UC patients divided into 3 age-groups: diagnosis ≥65 years, 40–64 years, and <40 years. Disease patterns, medical and surgical therapies, and risk factors for disease outcomes were analyzed. Results: Chronic active or relapsing disease accounts for 44% of patients with late-onset UC. Across all age-groups, these disease patterns require 3–6 times more steroids than remitting disease, but immunomodulators and, to a lesser extent, biologics are less frequently prescribed in the elderly. Advanced age, concomitant diseases and related therapies were found to be inversely associated with the use of immunomodulators or biologics, but not with surgery. Conclusions: The conclusion that late-onset UC follows a mild course may apply only to a subset of patients. an important percentage of elderly patients present with more aggressive disease. Since steroid use and surgery rates did not differ in this subgroup, lower use of immunosuppressive therapy and biologics may reflect concerns in prescribing these therapies in the elderly.